Nothing to complain about? Residents’ and relatives’ views on a “good life” and ethical challenges in nursing homes - Bollig, Georg; Gjengedal, Eva; Rosland, Jan Henrik (2016)
Background:Nursing home residents are a vulnerable population. Most of them suffer from multi-morbidity, while many have cognitive impairment or dementia and need care around the clock. Several ethical challenges in nursing homes have been described in the scientific literature. Most studies have used staff members as informants, some have focused on the relatives’ view, but substantial knowledge about the residents’ perspective is lacking.Objective:To study what nursing home residents and their relatives perceive as ethical challenges in Norwegian nursing homes.Research design:A qualitative design with in-depth interviews with nursing home residents, and focus-group interviews with relatives of nursing home residents. The digitally recorded interviews were transcribed verbatim. Analysis was based on Interpretive Description.Participants and research context:A total of 25 nursing home residents from nine nursing homes in Norway, and 18 relatives of nursing home residents from three of these nursing homes.Ethical considerations:This study was reported to and approved by the Regional Ethics Committee in Oslo, Norway.Findings and discussion:The main ethical challenges in Norwegian nursing homes from the residents’ and relatives’ perspective were as follows: (a) acceptance and adaptation, (b) well-being and a good life, (c) autonomy and self-determination, and (d) lack of resources. The relationship with the staff was of outmost importance and was experienced as both rewarding and problematic. None of the residents in our study mentioned ethical challenges connected to end-of-life care.Conclusion:Residents and relatives experience ethical challenges in Norwegian nursing homes, mostly connected to “everyday ethical issues.”
Keywords: residents’ view; relatives’ view; Nursing Homes; Ethics; Older people